Parasitic Gregarine blattarum Found Infecting American Cockroaches, Periplaneta americana, in a Population in Pulau Pinang, Malaysia - Zary Shariman Yahaya,; Nik Ahmad Irwan Izzaudin,; Ainul Farhana Abdul Razak, (Tropical Life Sciences Research, 2017)
A study on the prevalence of a common endoparasite in the wild population of the American cockroach was conducted in Penang Island using a trapping method at several sampling sites on the island. Gregarine blattarum was found in the digestive tract in 5 out of 115, or 4.35%, of the wild American cockroaches, Periplaneta americana, that were sampled. This is the first report in Malaysia of Gregarine blattarum in local American cockroaches. Satu kajian ke atas prevalens endoparasit biasa dalam populasi Lipas Amerika liar di Pulau Pinang dilakukan dengan kaedah perangkap di beberapa kawasan pensampelan di pulau tersebut. Gregarine blattarum ditemui dalam saluran pencernaan 5 daripada 115, atau 4.35%, dari Lipas Amerika liar, Periplaneta americana yang disampel. Ini merupakan penemuan pertama Gregarine blattarum di dalam Lipas Amerika tempatan yang dilaporkan di Malaysia.